Association between smoking and genital warts: longitudinal analysis. Issue 4 (26th July 2010) - Hansen, Bo Terning; Hagerup-Jenssen, Maria; Kjær, Susanne Krüger; Munk, Christian; Tryggvadottir, Laufey; Sparén, Pär; Liaw, Kai-Li; Nygård, Mari
Abstract : Objectives: To assess the association between smoking and the reported clinical diagnosis of genital warts. Methods: A sample of 58 094 women (aged 18–45) randomly drawn from the general female population of Denmark, Iceland, Norway and Sweden answered a questionnaire on lifestyle and health. Longitudinal data were reconstructed based on self report of age-specific events. In a Cox regression model, women who reported having been clinically diagnosed with genital warts were followed up until the age at first diagnosis, while women who reported never having been diagnosed with genital warts were censored at the age of interview. Age-specific smoking doses and ages at onset of smoking, sexual intercourse, condom use, hormonal contraceptive use, first pregnancy and alcohol drinking were included in the model as time-dependent covariates. The model also included lifetime number of coital partners and country of origin as fixed covariates. Results: Ever-smokers reported a lower age at first intercourse and more coital partners than never-smokers. The adjusted model showed that sexual behaviour strongly influenced the risk of being diagnosed with genital warts, and that smokers in addition had an increased risk compared with non-smokers (adjusted HR=1.27, 95% CI 1.17 to 1.37). There was also a modest additional dose–response effect of smoking, with smokers experiencing a 0.6% increased risk of being diagnosed with genital warts for each additional cigarette smoked daily (adjusted HR=1.006, 95% CI 1.001 to 1.012). Conclusions: Smokers experienced a moderately increased risk of being diagnosed with genital warts. This finding could be explained by the immunosuppressive effects of nicotine, or by confounding not accounted for in the adjusted model.